Development of antioxidative edible film from red dragon fruit peel extract with the addition of CMC and soy protein isolate - Lindriati, Triana; Yuwanti, Sih; Afriliana, Asmak; Sukoco, Aji; Budianto, Ivan Rivaldy; Azizah, Wafiq; Fadhiyah, Umrotus Shofiyatul (International Journal of Advances in Applied Sciences, 2025)
The red dragon fruit peels (RDFP) have a high content of pectin and total phenolic compounds. This research studied the development of RDFP be an antioxidative edible film. The RDFP was extracted by microwave to obtain high pectin and polyphenol content, and then the red dragon fruit peel extract (RDFPE) was used as a based material. The RDFPE was added with 5% (w/v) of carboxymethyl cellulose (CMC) and 10% (w/v) of soy protein isolate (SPI) to increase their tensile strength. The result showed that RDFPE potential to develop as an antioxidative edible film. There are different effects of CMC and SPI. The addition of CMC had a positive effect on total polyphenol and antioxidant properties but SPI had a negative effect. Against the peroxide number of peanut oils, all RDFPE films can inhibit. The effect of CMC and SPI on physical and mechanical properties were increasing thickness, and tensile strength decreasing transparency, solubility, also elongation. The FTIR showed a difference in macromolecule interaction between RDFPE with CMC and SPI. The interaction between RDFPE with CMC occurred with pectin while SPI interacted both with pectin and polyphenol. Thus, macromolecule interaction affected on physical, mechanical, and antioxidative properties of RDFPE edible films, and revealed that CMC was more suitable to add to RDFPE edible film.